Rhinovirus increases Moraxella catarrhalis adhesion to the respiratory epithelium - Dissanayake, Eishika; Brockman-Schneider, Rebecca A.; Stubbendieck, Reed M.; Helling, Britney A.; Zhang, Zhumin; Bochkov, Yury A.; Kirkham, Charmaine; Murphy, Timothy F.; Ober, Carole; Currie, Cameron R.; Gern, James E. (Frontiers in Cellular and Infection Microbiology, 2023)
Rhinovirus causes many types of respiratory illnesses, ranging from minor colds to exacerbations of asthma. Moraxella catarrhalis is an opportunistic pathogen that is increased in abundance during rhinovirus illnesses and asthma exacerbations and is associated with increased severity of illness through mechanisms that are ill-defined. We used a co-infection model of human airway epithelium differentiated at the air-liquid interface to test the hypothesis that RV infection promotes M. catarrhalis adhesion and survival on the respiratory epithelium Initial experiments showed that infection with M. catarrhalis alone did not damage the epithelium or induce cytokine production, but increased trans-epithelial electrical resistance, indicative of increased barrier function. In a co-infection model, infection with the more virulent rhinovirus-A and rhinovirus-C, but not the less virulent rhinovirus-B types, increased cell-associated M. catarrhalis. Immunofluorescent staining demonstrated that M. catarrhalis adhered to rhinovirus-infected ciliated epithelial cells and infected cells being extruded from the epithelium. RV induced pronounced changes in gene expression and secretion of inflammatory cytokines. In contrast, M. catarrhalis caused minimal effects and did not enhance RV-induced responses. Our results indicate that rhinovirus-A or C infection increases M. catarrhalis survival and cell association while M. catarrhalis infection alone does not cause cytopathology or epithelial inflammation. Our findings suggest that rhinovirus and M. catarrhalis co-infection could promote epithelial damage and more severe illness by amplifying leukocyte inflammatory responses at the epithelial surface.